Dyskurs akademicki jako praktyka społeczna. Zwrot dyskursywny i Społeczne Badania Szkolnictwa Wyższego - Wróblewska, Marta Natalia; Angermuller, Johannes (Kultura-Społeczeństwo-Edukacja, 2019)
One can broadly divide research on higher education settings into three strands investigating 1) the production of specialized scientific knowledge, 2) the dynamics of institutional power (academic decision-making and governance), 3) teaching and learning. In all three areas the notion of ‘discourse’ has been salient in the last decades. However, the term is often understood differently by researchers from different fields, and the respective disciplines haven’t always been receptive one to another. In the paper we present an overview of discursive approaches to the study of higher education in 1) social theory, poststructuralism in particular, and 2) linguistics. We explain the outlook on discourse which is prevalent in these areas and present the most significant studies on higher education contexts conducted within them. We argue that while social theory often lacks analytical detail and focus on empirical objects, linguistics on the other hand does not account for the way practices produce and reproduce social order. Therefore, a study of academic discourse drawing on both strands would enable putting forward a robust theory and a precise methodology. In the last section of the paper we present an outline of such a field informed by both poststructuralism and pragmatics – Social Studies of Higher Education.